A CASE STUDY OF CLASH DETECTION FOR EARLY DESIGN PHASES IN BUILDING INFORMATION MODELLING - Veli Mustafa Yönder; Hasan Burak Çavka (Livenarch+ Journal)
The utilization of digital modeling, monitoring, and simulation techniques in architectural and engineering projects at a real-world scale, following a predetermined workflow schedule, presents numerous advantages to key players and users involved in the construction process. Building information modeling and one of its associated advantages, clash/overlap detection, can play an important role during the initial stages of design development. The analysis of clash detection, which is a method that effectively identifies the overlap between spatial and three-dimensional geometric entities, facilitates a feedback-based design approach. The process of identifying and analyzing clashes can be conducted prior to the implementation phase, so guaranteeing long-term viability in relation to both temporal and financial aspects. In the context of this work, an examination of the available literature was conducted utilizing bibliometric approaches to get insight into the theoretical underpinnings of clash detection. In the present situation, significant clusters were acquired. In the methodology section, the modeling of the architectural design and structural project design for a two-storey architecture student center (ASC) project, spanning roughly 1200 square meters, was undertaken. The architectural and structural concepts of this project were designed using Autodesk Revit 2020 software, which is one of the building information modeling tools. Subsequently, clash detection analysis was employed. The analysis of clash detection was carried by using Autodesk Navisworks Manage 2020 software. The clashes, both soft and hard, were categorized and examined based on the achieved outcomes.